Lived experiences of patients with hypertension in managing daily life challenges: A phenomenological study - Mehta, Arjun; Sharma, Priya; Petel, Rahul; Reddy, Ananya (Indonesian Journal of Health Services, 2025)
Background: Hypertension is a major global health problem that not only leads to serious medical complications but also significantly impacts patients’ psychological, social, and daily life functioning. Despite the availability of effective pharmacological and non-pharmacological interventions, many individuals continue to struggle with uncontrolled blood pressure due to lifestyle, emotional, and systemic barriers. Understanding the lived experiences of patients is crucial for developing patient-centered interventions. Objective: This study aimed to explore the lived experiences of patients with hypertension in managing daily life challenges, focusing on their burdens, coping strategies, and interactions with healthcare systems. Methods: A qualitative study with a phenomenological approach was conducted in a referral hospital and selected community health centers. A total of 18 participants with a confirmed diagnosis of hypertension were recruited purposively. Data were collected through in-depth, semi-structured interviews and analyzed using Colaizzi’s descriptive phenomenological method. Themes and subthemes were developed to capture participants’ voices and experiences. Results: Three major themes emerged: (1) physical and emotional burdens, which included disruption of daily activities and fear of complications; (2) navigating lifestyle modifications, encompassing struggles with dietary restrictions and difficulties in maintaining medication and exercise routines; and (3) coping strategies and sources of resilience, which highlighted the role of social and familial support and spiritual as well as personal coping mechanisms. These themes demonstrated that patients face persistent barriers in managing hypertension but also develop adaptive strategies to sustain daily life. Conclusion: Living with hypertension involves multidimensional challenges beyond biomedical management, including psychological, social, cultural, and spiritual aspects. Patients often struggle with adherence to treatment and lifestyle modifications but demonstrate resilience through social support and personal coping strategies.